Protein Kinase C-α and ERK1/2 Mediate Mitochondrial Dysfunction, Decreases in Active Na(+) Transport, and Cisplatin-induced Apoptosis in Renal Cells - Nowak, Grażyna (2002)
Initiation of apoptosis by many agents is preceded by mitochondrial dysfunction and depolarization of the mitochondrial inner membrane. Here we demonstrate that, in renal proximal tubular cells (RPTC), cisplatin induces mitochondrial dysfunction associated with hyperpolarization of the mitochondrial membrane and that these events are mediated by protein kinase C (PKC)-α and ERK1/2. Cisplatin induced sustained decreases in RPTC respiration, oxidative phosphorylation, and increases in the mitochondrial transmembrane potential (ΔΨ(m)), which were preceded by the inhibition of F(0)F(1)-ATPase and cytochrome c release from the mitochondria, accompanied by caspase-3 activation, and followed by RPTC apoptosis. Cisplatin also decreased active Na(+) transport as a result, in part, of the inhibition of Na(+)/K(+)-ATPase. These changes were preceded by PKC-α and ERK1/2 activation. Inhibition of cisplatin-induced PKC-α and ERK1/2 activation using Go6976 and PD98059, respectively, abolished increases in ΔΨ(m), diminished decreases in oxidative phosphorylation, active Na(+) transport, and decreased caspase-3 activation without blocking cytochrome c release. Caspase inhibitor benzyloxycarbonyl-Val-Ala-Asp-fluoromethylketone (zVAD-fmk) did not prevent increases in ΔΨ(m). Furthermore, inhibition of PKC-α did not prevent cisplatin-induced ERK1/2 activation. We concluded that in RPTC: 1) cisplatin-induced mitochondrial dysfunction, decreases in active Na(+) transport, and apoptosis are mediated by PKC-α and ERK1/2; 2) PKC-α and ERK1/2 mediate activation of caspase-3 by acting downstream of cytochrome c release from mitochondria; and 3) ERK1/2 activation by cisplatin occurs through a PKC-α-independent pathway.